-11=3(x-7)-8x

Simple and best practice solution for -11=3(x-7)-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11=3(x-7)-8x equation:



-11=3(x-7)-8x
We move all terms to the left:
-11-(3(x-7)-8x)=0
We calculate terms in parentheses: -(3(x-7)-8x), so:
3(x-7)-8x
We add all the numbers together, and all the variables
-8x+3(x-7)
We multiply parentheses
-8x+3x-21
We add all the numbers together, and all the variables
-5x-21
Back to the equation:
-(-5x-21)
We get rid of parentheses
5x+21-11=0
We add all the numbers together, and all the variables
5x+10=0
We move all terms containing x to the left, all other terms to the right
5x=-10
x=-10/5
x=-2

See similar equations:

| 4x^2-64x+232=0 | | 8x4−42x3+29x2−42x+8=0 | | 8.x+x+x+x=64 | | 5.2x=80 | | (2p^2+4p)/(p^2+4p+3)=0 | | 1/2(16y-32)=3y-12+5y-4 | | 4^2=(x+3)3 | | 2x^2-27x-45=0 | | 5/8g-8=1/8g | | 5m−15=−5m= | | 12(16y-32)=3y-12+5y-4 | | 8y=54+2y | | 4y/5y=20 | | 20p-10=12p+54 | | ½h=15 | | 5z-2=8z+1 | | 12(x+3)=10(x) | | 8x^2=3–10x | | 2x^2+44x=0 | | 56+-3x=41 | | x^2-20x+82=-17 | | 9u=10.8 | | 9(p-1)=10(p-4) | | x^2-5x-78=6 | | x^2-5x-78=-6 | | 41-4x=13 | | x^2-5x-78=-15 | | c=1/4c-10 | | 113+-6x=53 | | x^2-17x+57=-15 | | 2^2-17x+57=-15 | | 8−2v=–5v−10 |

Equations solver categories